Application of Riemann-Liouville fractional integral to fuzzy differential subordination of analytic univalent functions - NILAPGOL, Sarika K.; SHELAKE, Girish D.; JIRAGE, Priyanka D. (Studia Universitatis Babeș-Bolyai Mathematica, 2025)
This paper focuses on geometric function theory, a subfield of complex analysis that has been adapted for fuzzy set analysis. A number of novel findings that are applicable to this class are found by applying the concept of fuzzy differential subordination. Interesting corollaries are discovered using specific functions, and an example illustrates the practical usage of the results. Mathematics Subject Classification (2010): 30C45, 30A10. Received 10 October 2024; Accepted 02 July 2025.